The potential of intracellular 13C MR spectroscopy to study the absolute configuration of endogenous and polarized alanine - Leksa, Natalia; Pękala, Anna; Pardak, Piotr; Dziedzic, Rafał; Bartusik-Aebisher, Dorota; Filip, Rafał; Galiniak, Sabina; Aebisher, David (European Journal of Clinical and Experimental Medicine, 2020)
<p class="rtejustify" style="box-sizing: border-box; margin: 0px 0px 1em; line-height: 20px; color: #010101; font-size: 14px; text-align: justify; font-family: Lato, sans-serif; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400; letter-spacing: 0.1px; orphans: 2; text-indent: 0px; text-transform: none; widows: 2; word-spacing: 0px; -webkit-text-stroke-width: 0px; white-space: normal; background-color: #ffffff; text-decoration-thickness: initial; text-decoration-style: initial; text-decoration-color: initial;">Introduction. Quantitative and accurate monitoring of tumor makes hyperpolarized carbon (13C) Magnetic Resonance Imaging and Spectroscopy (MRI/S) a powerful tool for in vivo metabolic and structural study. Moreover, the studies of the properties and functions in tumor tissue of the compounds of carbon (C) that are organic, are fundamental to tumor biochemistry. <p class="rtejustify" style="box-sizing: border-box; margin: 0px 0px 1em; line-height: 20px; color: #010101; font-size: 14px; text-align: justify; font-family: Lato, sans-serif; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400; letter-spacing: 0.1px; orphans: 2; text-indent: 0px; text-transform: none; widows: 2; word-spacing: 0px; -webkit-text-stroke-width: 0px; white-space: normal; background-color: #ffffff; text-decoration-thickness: initial; text-decoration-style: initial; text-decoration-color: initial;">Aim. To review 13C MR spectroscopy to study the absolute configuration of endogenous and polarized alanine Material and methods. An analysis of literature regarding 13C MR spectroscopy of polarized alanine. <p class="rtejustify" style="box-sizing: border-box; margin: 0px 0px 1em; line-height: 20px; color: #010101; font-size: 14px; text-align: justify; font-family: Lato, sans-serif; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400; letter-spacing: 0.1px; orphans: 2; text-indent: 0px; text-transform: none; widows: 2; word-spacing: 0px; -webkit-text-stroke-width: 0px; white-space: normal; background-color: #ffffff; text-decoration-thickness: initial; text-decoration-style: initial; text-decoration-color: initial;">Results. Current evidence suggests that the determination of absolute configurations of amino acids play significant role in physiological mechanisms during tumor growth and treatment. <p class="rtejustify" style="box-sizing: border-box; margin: 0px 0px 1em; line-height: 20px; color: #010101; font-size: 14px; text-align: justify; font-family: Lato, sans-serif; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400; letter-spacing: 0.1px; orphans: 2; text-indent: 0px; text-transform: none; widows: 2; word-spacing: 0px; -webkit-text-stroke-width: 0px; white-space: normal; background-color: #ffffff; text-decoration-thickness: initial; text-decoration-style: initial; text-decoration-color: initial;">Conclusions. Nearly 50% nuclear polarization for 13C can be achieved in various organic molecules when Dynamic Nuclear Polarization DNP is performed in a strong magnetic field and at cryogenic temperatures.